Financial Capital and Immigrant Self-Employment: Evidence from a Swedish Reform - Lina Aldén; Mats Hammarstedt; Chizheng Miao (Research Institute of Industrial Economics (IFN), 2020)
We study the role of capital requirement in immigrants' self-employment decision with the help of a reform implemented in Sweden in 2010 which reduced capital requirements for limited liability companies. For both men and women, the reform increased both the probability of starting a limited liability firm and the probability of changing corporate form for those self-employed prior to the reform. We found that the reform affected immigrants and natives differently. Natives primarily responded to the reform by changing corporate form whereas immigrant men, especially those originating from the Middle East, responded to the reform by starting limited liability firms. Small differences emerge when we compare native women with immigrant women. Finally, it is the wage employed who start a limited liability business in the post-reform period, underlining the fact that access to financial capital is an obstacle for wage-employed individuals who opt for self-employment. This is true for both immigrants and natives. In contrast, more marginalised groups (i.e. unemployed immigrants), do not respond to the reform by starting limited liability firms.
Keywords: J15; J68; L26; L51; 330; Self-employment; Financial capital; Limited liability; Immigrants